Metaphor of Colors in Indonesian and its Equivalence in German - Merry Lapasau (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
Metaphor is a form of speech or phrase that refers to one peculiar thing by mentioning another thing to get a rhetorical effect. The use of metaphor can explain the hidden similarity between two ideas of thought. This paper analyzes metaphors that use color names in Indonesian and their equivalences in German. Through metaphorical analysis, it can be expressed and compared on habits, implied knowledge, social representation of cultural diversity which at the same time reflects the norms embodied in the language user community in Indonesia and Germany. Data obtained from KBBI (2008) and Wahrig dictionary (2009). The research method is qualitative descriptive. The colors are distinguished in primary colors (red, yellow, and blue) and neutral colors (black and white). The results show that there are color metaphors in all primary and neutral colors in the two languages. Metaphors are used to express feelings (sad, happy, envy, angry), express ingenuity, hope, honesty, courage and so on. On the contrary, through color metaphors we can also criticize dishonesty, bad nature, ignorance evil and so on.